A flood of communications in a drought: a frame analysis of the City of Cape Town's communications during the 2017-2018 water crisis - Hill, Erin (Department of Environmental and Geographical Science, 2021)
Like many other urban areas around the world, Cape Town, South Africa relies on governmental management authorities to ensure water supply. Recently, a three year drought from 2015 to 2018 caused a major water shortage, threatening water supply to the city. In response, the City engaged in multiple mitigation efforts, amongst which was a major communications campaign to inform the public and encourage conservation behaviour. Drawing on literature on water crisis management and framing theory, this thesis analyses how the water crisis was framed in communications made available online by the City of Cape Town (CCT) to the public between March 2017 and March 2018. To answer this question, the project adopted a frames study approach to determine the types and characteristics of communication items released by the City of Cape Town, as the water managing authority, during the recent water crisis. The study established that a range of frames were employed by the CCT in communicating the drought. Through an analysis of the trends in the framing of the water crisis messages the study further identified the shifts in framing and messaging throughout the water crisis response period. Six key frames were identified, namely ‘the City success story'; ‘obscurity and ambiguity'; ‘consumption is key'; ‘the situation is controllable'; ‘together we can beat the drought'; and ‘us versus them'. It was found that while there may have been a lack of strategic planning regarding public communications which resulted in conflated messages, the City's communications campaign was nonetheless effective in that it correlated with a significant drop in private – individual and household – water consumption which delayed Day Zero (when water supply would be cut-off and daily water rations would only be available at collection points for the public). The key implication of this study is that despite contradictions, idiosyncrasies and lack of planning, a heterogenous range of messages in communicating a crisis can reach and evoke appropriate responses from multiple audiences of the public.